Customized corneal crosslinking for treatment of progressive keratoconus: Clinical and OCT outcomes using a transepithelial approach with supplemental oxygen. Issue 12 (December 2020) - Mazzotta, Cosimo; Sgheri, Arianna; Bagaglia, Simone Alex; Rechichi, Miguel; Di Maggio, Alessandro
Abstract : Epithelium-on, customized corneal crosslinking with supplemental oxygen delivery resulted in clinically and statistically significant flattening of the apex region of keratoconus and reduction in corneal higher-order aberrations without adverse events. Abstract : Purpose: To evaluate the outcomes of customized corneal crosslinking (CXL) for treatment of progressive keratoconus (KC) using a transepithelial approach with supplemental oxygen. Setting: Siena Crosslinking Center, Siena, Italy. Design: Prospective interventional case series. Methods: Twenty-seven eyes of 24 patients (mean age 29.3 ± 7.3 years) with progressive KC underwent customized corneal CXL using a transepithelial approach with supplemental oxygen. Ultraviolet (UV)-A irradiation of 365 nm wavelength was delivered in an accelerated (30 mW/cm 2 ) pulsed-light UV light exposure in a 2-zone elliptical pattern. A total dose of 10 J/cm 2 was delivered at the KC apex, surrounded by a broadbeam spot of 7.2 J/cm 2 . After 0.25% riboflavin corneal soaking, the UV-A irradiation was initiated in the presence of additional oxygen (≥90% concentration) delivered through special goggles connected to an oxygen delivery system (flow-rate 2.5 liters per minute). Key outcome measures included corrected distance visual acuity (CDVA), keratometry (AK, K1, K2, and K-average), corneal higher-order aberrations, topographic and manifest cylinder, corneal optical coherence tomography (OCT) demarcation line, and endothelial cell count. Results: Of the 27 eyes studied, a significant improvement of CDVA was recorded at 6-month follow-up visits, from baseline 0.19 ± 0.06 logarithm of the minimum angle of resolution (logMAR) to 0.11 ± 0.04 logMAR ( P < .05). Significant flattening of steep keratometry (K2) was reported with mean change of −1.9 diopters (D) ( P < .05), and coma values improved from 0.47 ± 0.28 µm to 0.28 ± 0.16 µm ( P < .05). OCT revealed 2 demarcation lines at mean depths of 218.23 ± 43.32 µm and 325.71 ± 39.70 µm. Conclusions: In this series, customized CXL using a transepithelial approach with intraoperative supplemental oxygen resulted in clinically meaningful improvements in corneal curvature and CDVA without significant adverse events.